The DREAMS experiment flown on the ExoMars 2016 mission for the study of Martian environment during the dust storm season. (July 2018) - ,; Harri, A.-M.; Montmessin, F.; Wilson, C.; Rodríguez, I. Arruego; Abbaki, S.; Apestigue, V.; Bellucci, G.; Berthelier, J.-J.; Calcutt, S.B.; Forget, F.; Genzer, M.; et al.
Highlights: DREAMS flew on Schiaparelli lander of ExoMars mission and landed on Mars in 2016. No operation was possible after crash but operation of the unit was nominal in cruise. The instrument would operate autonomously for 2 sols sampling data of atmosphere. The instrument would investigate key parameters of atmosphere for future manned missions. Three DREAMS models were fully tested during the qualification test campaign. Abstract: The DREAMS (Dust characterization, Risk assessment and Environment Analyser on the Martian Surface) instrument on Schiaparelli lander of ExoMars 2016 mission was an autonomous meteorological station designed to completely characterize the Martian atmosphere on surface, acquiring data not only on temperature, pressure, humidity, wind speed and its direction, but also on solar irradiance, dust opacity and atmospheric electrification; this comprehensive set of parameters would assist the quantification of risks and hazards for future manned exploration missions mainly related to the presence of airborne dust. Schiaparelli landing on Mars was in fact scheduled during the foreseen dust storm season (October 2016 in Meridiani Planum) allowing DREAMS to directly measure the characteristics of such extremely harsh environment. DREAMS instrument's architecture was based on a modular design developing custom boards for analog and digital channel conditioning, power distribution, on board data handling and communication with the lander. The boards, connected through a common backbone, were hosted in a central electronic unit assembly and connected to the external sensors with dedicated harness. Designed with very limited mass and an optimized energy consumption, DREAMS was successfully tested to operate autonomously, relying on its own power supply, for at least two Martian days (sols) after landing on the planet. A total of three flight models were fully qualified before launch through an extensive test campaign comprising electrical and functional testing, EMC verification and mechanical and thermal vacuum cycling; furthermore following the requirements for planetary protection, contamination control activities and assay sampling were conducted before model delivery for final integration on spacecraft. During the six months cruise to Mars following the successful launch of ExoMars on 14th March 2016, periodic check outs were conducted to verify instrument health check and update mission timelines for operation. Elaboration of housekeeping data showed that the behaviour of the whole instrument was nominal during the whole cruise. Unfortunately DREAMS was not able to operate on the surface of Mars, due to the known guidance anomaly during the descent that caused Schiaparelli to crash at landing. The adverse sequence of events at 4 km altitude anyway triggered the transition of the lander in surface operative mode, commanding switch on the DREAMS instrument, which was therefore able to correctly power on and send back housekeeping data. This proved the nominal performance of all DREAMS hardware before touchdown demonstrating the highest TRL of the unit for future missions. The spare models of DREAMS are currently in use at university premises for the development of autonomous units to be used in cubesat mission and in probes for stratospheric balloons launches in collaboration with Italian Space Agency.